Experimental investigations the effects of dusty, humidity and temperature conditions on chemical anchors - Çalışkan, Özlem; Aras, Murat; Ağdağ, Yılmaz (Revista de la Construcción. Journal of Construction, 2023)
Chemical anchor applications are frequently used to add new structural elements to existing structures. Chemical anchors can be applied quickly and easily, if anchors apply according to a detailed installation and cleaning procedure depending on environmental conditions and workmanship. In this work, the relationship between the axial tensile capacity of chemical anchors and the effect of dust, humidity, and temperature were examined as adverse conditions. The effect of using different conditions, anchorage diameters and embedment depth on the tensile strength of the anchors was evaluated. In the experimental study, anchors diameter 12, 16 and 20 mm were selected to be used as anchors. The depth of embedding was determined to be 5, 10, 15 and 20 times the diameter of used anchors. The initial stiffness, displacement ductility ratio, energy absorption capacity, failure modes, and safety levels according to ACI 318 were obtained by using the load-displacement curves. According to the parameters considered in the experimental program, the most unfavorable situation was obtained in anchors embedded in a wet environment. In addition, it was observed that the diameter of the drilled holes causes a decrease in the axial tensile capacity by increasing the exposure time of the anchors to water and temperature.